2015
DOI: 10.4070/kcj.2015.45.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Acute ST-Segment Elevation Myocardial Infarction in Younger Korean Adults

Abstract: Background and ObjectivesThis study aims to investigate the clinical features, angiographic findings, and outcomes of younger Korean ST-segment elevation myocardial infarction (STEMI) patients.Subjects and MethodsWe analyzed major adverse cardiac events (MACE) in the Korea Acute Myocardial Infarction Registry from November 2005 to October 2010. The registered patients were divided into two groups; young age group (<65 years) and old age group (≥65 years).ResultsThe young age group included 5281 patients (age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…Previous studies have used serum sodium levels on admission for evaluating the impact of hyponatremia on adverse outcomes and also included all hospitalized patients with AMI, irrespective of in-hospital death or survival [6][7][8][9][10][11]. Therefore, these studies had a higher number of ill patients with old age, high Killip class, low LVEF, and/or high NT-ProBNP levels, which are [19][20][21][22][23]. In the present study, we have excluded patients with in-hospital death and used serum sodium levels at discharge, when patients are considered hemodynamically stable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used serum sodium levels on admission for evaluating the impact of hyponatremia on adverse outcomes and also included all hospitalized patients with AMI, irrespective of in-hospital death or survival [6][7][8][9][10][11]. Therefore, these studies had a higher number of ill patients with old age, high Killip class, low LVEF, and/or high NT-ProBNP levels, which are [19][20][21][22][23]. In the present study, we have excluded patients with in-hospital death and used serum sodium levels at discharge, when patients are considered hemodynamically stable.…”
Section: Discussionmentioning
confidence: 99%
“…The primary PCI rate for STEMI in Korea was reported to be more than 95% in a recent analysis, and in this study we have attempted to determine the clinical impact of AF in STE-MI patients who were treated appropriately with primary PCI in a Korean population. 13,20) We thought it would be very important to clarify the clinical importance and prognosis of any type of AF documented on ER arrival, irrespective of whether it was persistent or new onset AF, in STEMI patients who were treated with primary PCI in the modern era of cardiology practice. Based on this background clinical concept, we selected only STEMI patients in the KAMIR database who presented within 12 hours after chest pain onset and underwent primary PCI appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…12) Registration started in 2005 with 41 general and educational hospitals that had catheterization laboratories and were performing primary PCI, but is now being carried out by 18 carefully selected educational hospitals. 12,13) A total of 46,591 patients with AMI were registered between 2006 and 2013, and the study is currently being continued through collaboration by the Korean Society of Cardiology and the Korean National Institute of Health. Study design : We analyzed the KAMIR database entries that were registered from January 2008 to September 2009 and identified 14,329 patients with AMI.…”
Section: Korea Acute Myocardial Infarction Registry (Kamir)mentioning
confidence: 99%
“…Recently, Lee et al 14 showed that younger Korean adults with STEMI have clinical outcomes similar to older aged patients and therefore, they should be treated intensively like the elderly patients. Previous studies have demonstrated that the young AMI group has a higher proportion of males, presenting with modifiable risk factors such as smoking, hyperlipidaemia, and being more overweight with respect to the older age group 15 16.…”
Section: Discussionmentioning
confidence: 99%